THEME: CURRICULUM DESIGN AND PLANNING IN INTENSIVE LANGUAGE LEARNING - Egamberdiyev Sardor,; Orziqulova Durdona, (Ustozlar uchun, 2025)
This article explores the essential elements of curriculum design and planning for intensive language learning programs. It delves into the key principles that guide the creation of an effective curriculum, such as setting clear objectives, integrating thematic and contextual approaches, ensuring a balanced development of language skills, and fostering cultural awareness. The article emphasizes the importance of scaffolding, progression, and continuous assessment in enabling learners to acquire language skills rapidly and effectively. Additionally, it highlights the need for flexibility to accommodate diverse learning styles and ensure the curriculum meets the varied needs of students. Ultimately, the article provides a comprehensive framework for developing an intensive language curriculum that supports both language acquisition and cultural understanding.